A dynamic adaptive electric field regulation strategy for stabilizing zinc anodes based on σ-electron donation - Hongxiang Zhao; Hua Yang; Jiayu Li; Yanwei Fu; Yu Zhao; Yuanshuai Wan; Yue Li; Yuliang Pang; Xingfa Qiu; Wenwen Duan; Weize Wang; Jiali Zhang; et al. (Chemical Engineering Journal, 2026)

Sodium pyrophosphate-induced actomyosin dissociation, thick filament depolymerization and protein conformation changes synergistically enhance the solubility of myofibrillar proteins - Jiafeng Xu; Meihan Wang; Siyu Chen; Xinyu Fu; Xinyue Xie; Jun-hua Shao; Yanwei Zhang; Chunqiang Li (Food Chemistry, 2026)

Corrigendum to “Rapid detection of Streptococcus agalactiae in tilapia using RPA-PfAgo detection systems” [Aquaculture, Volume 619, 30 May 2026, 743875] - Xiaojing Xia; Jiahui Fu; Qianlei Zhu; Kexin Wang; Jingjing Li; Xujie Zhao; Lei Wang; Yanwei Li; Chengshui Liao; Yimin Wang; Yueyu Bai; Yilin Bai; et al. (Aquaculture, 2026)

Rapid detection of Streptococcus agalactiae in tilapia using RPA-PfAgo detection systems - Xiaojing Xia; Jiahui Fu; Qianlei Zhu; Kexin Wang; Jingjing Li; Xujie Zhao; Lei Wang; Yanwei Li; Chengshui Liao; Yimin Wang; Yueyu Bai; Yilin Bai; et al. (Aquaculture, 2026)

Mussel-inspired coating anchored polyquaternium functionalized nonwoven fabrics for microplastic adsorption - Yuanshuai Wan; Yanjun Jia; Yonggui Guo; Jianteng Sun; Maofeng Liang; Lichao Gao; Haidong Cao; Tiantian Liu; Hongxiang Zhao; Yuliang Pang; Yanwei Fu; Yu Zhao; et al. (Journal of Environmental Chemical Engineering, 2025)

Polychlorinated biphenyl pollution as an unintentional major contaminant in the Pearl River Delta, China - Hongbing Wang; Chenglong Wei; Guowei Fu; Daheng Zhang; Miao Fu; Junyi Jiang; Yue Long; Yanwei Song (Environmental Research, 2025)

Identification and characterization of miRNAs and targets in two poplar varieties with different resistance in responses to Anoplophora glabripennis (Coleoptera) infestation - Zeqi Wang; Tiantian Fu; Chun Wang; Yuzhang Yang; Xiaoqian Yang; Jiahao Liu; Ruen Yu; Hongkun Ji; Yuanlong Wang; Tianliang Wang; Jieru Li; Yanwei Wang (Plant Science, 2025)

Elucidating enantioselective toxicity mechanism of chiral fungicide tebuconazole to Eisenia fetida: Phenotypic analysis and multi-omics integration - Ziyang Diao; Jiqiang Fu; Jingyang Zhao; Jishi Wang; Wenjing Liu; Yanwei Zhang; Zeying He (Journal of Hazardous Materials, 2025)

Selection of microRNA expression reference genes for RT-qPCR in poplar root under low nitrogen stress - Chun Wang; Tiantian Fu; Zeqi Wang; Jiahao Liu; Siyu Hou; Yiyi Yin; Xiaoqian Yang; Dandan Xiao; Yanwei Wang (Journal of Plant Biochemistry and Biotechnology, 2025)

miRNA-seq analysis revealed a potential strategy underlying poplar root responses to low nitrogen stress - Chun Wang; Tiantian Fu; Zeqi Wang; Siyu Hou; Kaijing Rong; Jing Wang; Yiyi Yin; Xiaoqian Yang; Ruen Yu; Dandan Xiao; Yanwei Wang (Planta, 2025)

Spatial distribution characteristics, ecological risk assessment, and source analysis of heavy metal(loid)s in surface sediments of the nearshore area of Qionghai - Junyi Jiang; Miao Fu; Jianying Yang; Yanwei Song; Guowei Fu; Hongbing Wang; Cong Lin; Yang Wang (Frontiers in Marine Science, 2024)
To understand the pollution characteristics and potential sources of heavy metal(loid)s in the nearshore sediments of Qionghai, 93 surface sediment samples were collected from the region. The concentrations of 20 elements, including Fe, Mg, Ca, Ti, Mn, Ba, Cr, Sr, Ni, Cu, Zr, As, Hg, Se, Be, Co, Mo, Cd, Ga, and Pb, were measured. The extent of contamination and ecological risk posed by these heavy metals/metalloids were evaluated using the geo-accumulation index, potential ecological risk index, and Nemerow comprehensive risk index. Additionally, correlation analysis, principal component analysis (PCA), and positive matrix factorization (PMF) were employed to identify the potential sources of these elements in the sediments. The findings reveal the following: (1) The mean concentrations of Fe, Ca, Mg, Ti, Cu, Sr, Zr, Mo, Cd, Pb, Hg, As, and Se exceed the background values for shallow sea sediments in China. Notably, Ca, Ti, Sr, Zr, Mo, Hg, and As exhibit coefficients of variation greater than 51%, indicating significant spatial variability primarily driven by anthropogenic activities. (2) The ecological risk assessment identifies Sr, Hg, and As as the principal pollutants and key potential ecological risk factors in the study area, necessitating prioritization in subsequent monitoring efforts. (3) Correlation and source analysis suggest that As and Mn primarily originate from agricultural activities, Sr, Ca, and Mg from aquaculture, Zr, Ti, Mo, Se, Pb, Be, Co, Cu, Ga, Ni, Fe, and Cd from natural sources, and Hg, Ba, and Cr from transportation sources. Additionally, this study identified Sr, Hg, and As as the primary pollutants in the Qionghai nearshore area, with sources predominantly linked to agriculture, aquaculture, and traffic. Regular monitoring will help track the effectiveness of implemented control measures and provide data for ongoing risk assessments, ensuring the protection and sustainability of the marine environment.

Distribution, sources, impact factors and ecological risks of sediment heavy metals from typical estuarine wetlands in tropical islands - Kaizhe Fu; Zeheng Chen; Cheng Huang; Yuanyuan Chen; Dongming Wu; Xiwen Li; Yanwei Song; Weipin Ding; Xiujiu Yang; Junqiao Long (Estuarine, Coastal and Shelf Science, 2024)

Research on comprehensive assessment of coastal erosion intensity based on multi index method - Guowei Fu; Mingguang He; Xiaofeng Chen; Miao Fu; Yanwei Song; Chenglong Wei; Hongbing Wang; Daheng Zhang (Frontiers in Marine Science, 2024)
The intensity of coastal erosion is a measure of the strength of erosion processes affecting coastal areas. Traditionally, assessments of coastal erosion intensity have relied on singular indices, such as the rate of shoreline retreat or erosion, often prioritizing higher rates over lower ones. This approach, however, lacks comprehensive consideration and scientific rigor. In this study, we adopt a more holistic approach by examining the Qionghai-Wanning coast on the eastern side of Hainan Island. We selected four indices that reflect local conditions and influence coastal erosion strength: Annual rate of shoreline change (T1), Beach annual down-cutting rate (T2), Beach slope (T3), Average particle size of the beach (T4). These indices were used to comprehensively evaluate the erosion intensity of the Qionghai-Wanning coast. The evaluation results categorized the study area into six grades: serious erosion (3.45%), strong erosion (6.90%), erosion (20.69%), micro erosion (44.38%), stabilization (20.69%), and accretion (3.45%). The findings indicate that, under the broader environmental trends of global warming and rising sea levels, most sandy coasts exhibit micro-erosion intensity. Areas experiencing strong and serious erosion are predominantly influenced by human activities, such as those occurring in promenade bays, artificial islands, and harbors. To further understand the relationship between these factors and erosion intensity, we employed the Spearman correlation coefficient method. The analysis revealed that the T1 and the T2 are the primary factors influencing coastal erosion intensity, with the T4 serving as a secondary factor. These factors collectively impact the force and energy absorption of the coast through wave and tidal actions, ultimately determining the intensity of coastal erosion. The multi-index assessment method for coastal erosion intensity demonstrated an accuracy of 82.75%, providing a scientific basis for the management, protection, and restoration of coastal areas.

Assessment of the community status of seagrass bed and its relationship with environmental characteristics in Wenchang, Hainan Island, China - Miao Fu; Junyi Jiang; Dacheng Wang; Guowei Fu; Yanwei Song; Hongbing Wang; Daheng Zhang (Frontiers in Marine Science, 2024)
As one of the typical coastal ecosystems, seagrass bed has important ecological service functions. In order to enrich the basic data of multispecies tropical seagrass beds, the main controlling factors affecting the community status of seagrass were identified. In this study, the species, distribution and community characteristics of seagrass in Wenchang were investigated at five stations in 2023, and Spearman correlation analysis and Redundancy analysis were used to investigate the relationship between seagrass and environmental characteristics. The results showed that there were 7 species of seagrass belonging to 5 genera in 2 families along Wenchang coast, including Enhalus acoroides , Thalassia hemprichii , Cymodocea rotundata , Cymodocea serrulata , Halophila ovalis , Halophila minor and Halodule uninervis . The distribution of seagrass beds in Wenchang showed an obvious trend of degradation. Except for the relatively stable of seagrass beds in the central part of Wenchang, the seagrass beds on both the north and south sides decreased significantly, and the coverage of seagrass beds decreased from 24.31% in 2016 to 21.0% in 2020, and further decreased to 20.67% in 2023. The data showed that the coverage and aboveground biomass of seagrass were significantly positively correlated with temperature, and the density of seagrass was significantly positively correlated with DO, but significantly negatively correlated with COD. In addition, increased nutrient salts in the water column could negatively affect seagrass bed. In order to promote the sustainable development of seagrass ecosystem and enhance the stability of seagrass habitat, it is suggested to rationally plan the aquaculture scale of the surrounding area; flexibly manage the rake snail, rake clam and other fishing activities, appropriately reduce the frequency of mining; and scientifically plan marine engineering to reduce the damage to seagrass bed.

Distribution Characteristics and Factors Controlling Different Phosphorus Fractions in the Soils and Sediments of an Inland Lagoon - Kun Yuan; Rui Wang; Bo He; Guowei Fu; Yanwei Song; Lixin Pei; Shichao Fan; Fangyi Gao (Journal of Marine Science and Engineering, 2024)
Lagoons, significant coastal wetlands, stand out for their vital role in the cycles and transformations of phosphorus. However, the relationship between the spatial distributions of various phosphorus forms in the soil and sediments of lagoon areas remains unclear. This study investigated the phosphorus fractions and distribution patterns in the soil and sediments from Shimei Inland Sea, Hainan Province, China, and identified the factors controlling phosphorus distribution and its relationship with lagoon eutrophication. The results revealed significant enrichment of inorganic phosphorus (IP) in the Shimei Inland Sea (64.1–679.0 mg/kg) and offshore areas (56–627.2 mg/kg), while organic phosphorus (OP) was relatively concentrated in land (60–744.3 mg/kg), suggesting that the productivity of the terrestrial ecosystem controlled the OP content and IP formed from the mineralization of OP was more likely to leach into the water and combine with minerals. Total phosphorus (TP) content was negatively affected by pH, and organic matter, cation exchange capacity and iron/aluminum oxides showed significant positive correlations with TP content. These findings highlighted the coupled impact of soil and sediment physicochemical properties on phosphorus enrichment and transformation, providing theoretical support for the ecological restoration of ecosystems in tropical coastal wetlands.

Flavor characteristics of semi-dried yellow croaker (Pseudosciaena crocea) with KCl and ultrasound under sodium-reduced conditions before and after low temperature vacuum heating - Junlong Mao; Jingjing Fu; Zhengyu Zhu; Zhenzhi Cao; Min Zhang; Yanwei Yuan; Tingting Chai; Yuewen Chen (Food Chemistry, 2023)

Spatiotemporal evolution and convergence of agricultural eco-efficiency in the middle reaches of the Yangtze River - Tiangui Lv; Shufei Fu; Xinmin Zhang; Han Hu; Yanwei Zhang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Synergistic/antagonistic effects of nitrate/ammonium enrichment on fatty acid biosynthesis and translocation in coral under heat stress - Jingjing Zhang; Zanhui Huang; Yuanchao Li; Dinghui Fu; Qipei Li; Lixin Pei; Yanwei Song; Liang Chen; Hongwei Zhao; Shuh-Ji Kao (Science of The Total Environment, 2023)

Modeling nutrient flows from land to rivers and seas – A review and synthesis - Xiaoyang Shan; Zhiqiang Zhu; Jiyong Ma; Dinghui Fu; Yanwei Song; Qipei Li; Zanhui Huang; Lixin Pei; Hongwei Zhao (Marine Environmental Research, 2023)

Epitaxial growth of cactus-like heterojunction with perfect interface for efficient photoelectrochemical water splitting - Yaling Fu; Yanwei Wang; Yu Wu; Chuanzhen Feng; Huijuan Zhang; Yu Wang (Chemical Engineering Journal, 2023)

Characteristics and evaluation of coastal erosion vulnerability of typical coast on Hainan Island - GuoWei Fu; Chao Cao; KaiZhe Fu; YanWei Song; Kun Yuan; XiaoMing Wan; ZiAng Zhu; ZhaoFan Wang; ZanHui Huang (Frontiers in Marine Science, 2022)
Coastal erosion vulnerability assessment is widely used to assess the loss degree of coastal zone caused by erosion, and plays an important role in coastal natural resources protection, planning, management and decision-making. Based on the natural and social characteristics of the east coast of Qiongdong and the coastal erosion vulnerability index (CVI) method, this study selected 8 assessment indicators, such as shoreline change rate (U1). The Delphi method and the entropy weight method were used to calculate the comprehensive index weight, combined with CVI method and geographic information system (GIS) technology, to quantitatively evaluate the temporal and spatial distribution characteristics of typical coastal erosion vulnerability such as coral reefs in the east of Hainan Island. The study area was divided into 5 grades: very low (31%), low (10%), moderate (28%), high (24%) and high vulnerability (7%), and the overall performance was moderate erosion vulnerability. The research showed that the interannual downward rate erosion of beach (U3) and the rate of change of the isobath (U2) of the beach were the main controlling factors affecting the vulnerability of coastal erosion in the study area, and the coastal dynamic factor had a greater impact than the other two factors. As a natural barrier, the coral reefs in the study area had good wave absorption and energy reduction, and the coral reef coasts showed low coastal erosion vulnerability, due to the complex hydrodynamic characteristics, estuary coasts is the most vulnerable areas. The verification results of the ROC-AUC method showed that the accuracy of erosion vulnerability was 68.9%, which provided an important reference for the ecological restoration of tropical coral reef biological coasts and the development and management of the Hainan Qiongdong coastal zone.

Physiological functions of urea transporter B - Lanying Yu; Tiantian Liu; Shuang Fu; Li Li; Xiaoping Meng; Xin Su; Zhanfeng Xie; Jiayan Ren; Yan Meng; Xuejiao Lv; Yanwei Du (Pflügers Archiv - European Journal of Physiology, 2019)
Urea transporters (UTs) are membrane proteins in the urea transporter protein A (UT-A) and urea transporter protein B (UT-B) families. UT-B is mainly expressed in endothelial cell membrane of the renal medulla and in other tissues, including the brain, heart, pancreas, colon, bladder, bone marrow, and cochlea. UT-B is responsible for the maintenance of urea concentration, male reproductive function, blood pressure, bone metabolism, and brain astrocyte and cardiac functions. Its deficiency and dysfunction contribute to the pathogenesis of many diseases. Actually, UT-B deficiency increases the sensitivity of bladder epithelial cells to apoptosis triggers in mice and UT-B-null mice develop II-III atrioventricular block and depression. The expression of UT-B in the rumen of cow and sheep may participate in digestive function. However, there is no systemic review to discuss the UT-B functions. Here, we update research approaches to understanding the functions of UT-B.

Correction to: Adsorption antagonism and synergy of arsenate(V) and cadmium(II) onto Fe-modified rice straw biochars - Youchi Zhang; Jiajun Fan; Minglai Fu; Yong Sik Ok; Yanwei Hou; Chao Cai (Environmental Geochemistry and Health, 2019)

Adsorption antagonism and synergy of arsenate(V) and cadmium(II) onto Fe-modified rice straw biochars - Youchi Zhang; Jiajun Fan; Minglai Fu; Yong Sik Ok; Yanwei Hou; Chao Cai (Environmental Geochemistry and Health, 2019)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)